MATHEMATICS IN THE NURSING PROFESSION: STUDENT AND PROFESSIONAL NURSES' PERSPECTIVE - Ogbonnaya, Ugorji Iheanachor; Awoniyi, Florence (Universitas Pelita Harapan, 2021)
Mathematical knowledge and skill are needed by all students in their studies and future careers. Students’ perceived relevance of mathematics in their future careers influences their attitude towards learning mathematics. This study explored student and professional nurses' perceived relevance and application of mathematics in the nursing profession. A sample size of 301 nursing students in a University in Ghana and 12 professional nurses participated in the study. Data was collected using a questionnaire and interview and was analyzed using descriptive statistics and thematic analysis. The study revealed that both the professional and the student nurses perceived Statistics, Ratio and Rates, and Percentages as the topics in school mathematics that they find most relevant and applicable to their study and practice of nursing. It is recommended that the senior high school mathematics teachers may need to always share the professional applicability of any topic they teach, by using authentic and real-life situations in various professions.